ChemInform Abstract: Lewis Base Directed Cycloaddition Reactions of 2‐Pyrones and Alkynylaluminum Reagents. Issue 51 (17th December 2013) - Crepin, Damien F.; Harrity, Joseph P. A.
Abstract In situ prepared alkynylaluminum derivatives are used as novel 2π compounds in [4 + 2] cycloadditions with 2‐pyrans bearing amides or N‐heteroarenes as directing groups.